The Organizational Culture on Accounting Information Systems Quality and Implications on The Quality of Information - Susilawati, Christine Dwi Karya; Thiodora, Veranica (Universitas Pamulang, 2023)
Abstract A strong organizational culture is widely recognized and is often cited as the reason for the success of the organization, and vice versa, a weak organizational culture can cause problems for the organization. PT Frisian Flag Indonesia is one of the companies that is quite successful in Indonesia, and this success can be achieved because of the harmony between companies that have well socialized the organizational culture to their employees. The objectives to be achieved in this study were to determine the effect of organizational culture on the quality of the accounting information system and to determine the effect of the quality of the accounting information system on the quality of information at PT Frisian Flag Indonesia. The method used is Causal Explanatory, which identifies the causal relationship of various variables and phenomena that exist. The result of the research is that there is a partial influence of organizational culture variables on the quality of the accounting information system of PT Frisian Flag Indonesia Bandung branch with a t value of 5,909 with a significance level of 0,000 and there is a significant influence between the variables of the quality of accounting information systems partially on the quality of PT Frisian information. Flag of Indonesia Bandung branch with t value of 10,888 with a significance level of 0,000 Abstrak Budaya organisasi yang kuat diakui secara luas dan sering disebut-sebut sebagai alasan keberhasilan organisasi, begitu pula sebaliknya, budaya organisasi yang lemah dapat menimbulkan permasalahan bagi organisasi. PT Frisian Flag Indonesia merupakan salah satu perusahaan yang cukup sukses di Indonesia, dan keberhasilan tersebut dapat diraih karena adanya keharmonisan antar perusahaan yang telah mensosialisasikan dengan baik budaya organisasi kepada karyawannya. Tujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui pengaruh budaya organisasi terhadap kualitas sistem informasi akuntansi dan untuk mengetahui pengaruh kualitas sistem informasi akuntansi terhadap kualitas informasi pada PT Frisian Flag Indonesia. Metode yang digunakan adalah Causal Explanatory, yaitu mengidentifikasi hubungan sebab akibat dari berbagai variabel dan fenomena yang ada. Hasil penelitian terdapat pengaruh secara parsial variabel budaya organisasi terhadap kualitas sistem informasi akuntansi PT Frisian Flag Indonesia cabang Bandung dengan nilai t sebesar 5,909 dengan tingkat signifikansi 0,000 dan terdapat pengaruh yang signifikan antara variabel budaya organisasi terhadap kualitas sistem informasi akuntansi PT Frisian Flag Indonesia cabang Bandung dengan nilai t sebesar 5,909 dengan tingkat signifikansi 0,000. variabel kualitas sistem informasi akuntansi secara parsial terhadap kualitas informasi PT Frisian. Bendera Indonesia Cabang Bandung dengan nilai t hitung sebesar 10,888 dengan tingkat signifikansi 0,000.